Anniversaries in history of morphology in 2014 - Kutya, S. A. (Морфологія / Morphologia / Morfologìâ, 2014)
500 years ago, Andrei Vesalius (Andreas Vesalius, 1514-1564) was born - Flemish anatomist, the founder of scientific anatomy. He studied medicine in Louvain, Montpellier and Paris.